2009
DOI: 10.1159/000235858
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Visual Sensations Experienced during Pars Plana Vitrectomy under Retrobulbar Anesthesia

Abstract: Purpose: To investigate the visual sensations experienced by patients during vitrectomy under retrobulbar anesthesia. Methods: 30 men and 45 women with a mean age of 65.3 ± 10.6 years underwent vitrectomy under retrobulbar anesthesia for macular disease. 28 eyes had an idiopathic epiretinal membrane, 13 had an idiopathic macular hole, 32 had macular edema (17 diabetic retinopathy and 15 retinal vein occlusion), and 2 had submacular hemorrhage. 49 patients with nonmacular disease underwent similar vitrectomy pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The outlines of the tips of these instruments were not as sharp as those seen during vitreous surgery. [12][13][14] In addition, they were not as sharp as the images recorded during simulated vitrectomy in the model eye, 16,17 in which the instruments were closer to the posterior surface. The greater distance of the instruments in the anterior chamber to the posterior surface made the images cast on the posterior surface more blurred.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The outlines of the tips of these instruments were not as sharp as those seen during vitreous surgery. [12][13][14] In addition, they were not as sharp as the images recorded during simulated vitrectomy in the model eye, 16,17 in which the instruments were closer to the posterior surface. The greater distance of the instruments in the anterior chamber to the posterior surface made the images cast on the posterior surface more blurred.…”
Section: Discussionmentioning
confidence: 83%
“…[1][2][3][4][5] About 60% of the patients who reported seeing movements or moving objects also saw objects that resembled surgical instruments. [11][12][13][14] Although most of the descriptions have been verbal, one patient expressed her cataract surgical experiences through two paintings; one consisted of pink and blue rings, and the second consisted of a bright orange line she perceived for a short time. 6 The author suggested that these images represented the movement of a phacoemulsification probe into the eye with a possible stimulation of the color photoreceptors by the ultrasonographic energy.…”
Section: Introductionmentioning
confidence: 99%
“…A significant correlation has been found between the intraoperative visual sensations and the pre‐ or postoperative visual acuity (Sugisaka et al. 2007; Suigisaka et al. 2010).…”
Section: Discussionmentioning
confidence: 97%
“…2008). About 60% of the patients who reported seeing movements or moving objects also see surgical instruments (Suigisaka et al. 2010).…”
Section: Introductionmentioning
confidence: 99%
“…3 Indeed, some authors are even using IVT therapeutic agents for relatively rare disorders, such as central serous chorioretinopathy. 3 Patients' visual perceptions and experiences induced by frequently performed ophthalmic surgical procedures, such as cataract surgery (under topical [10][11][12][13][14][15] and regional anesthesia [11][12][13][14]16,17 ), glaucoma filtration surgery, 18 and vitreoretinal surgery, [19][20][21][22] are well documented. Indeed, the beneficial effect of preoperative counseling with respect to known and anticipated visual experiences during phacoemulsification cataract surgery, under topical anesthesia, in terms of reducing patients' fear, has been described.…”
Section: Introductionmentioning
confidence: 99%